To solve the system of equations:
-3x - 4y = -23 ...(1)
3x - 5y = 5 ...(2)
We can use the elimination method to solve the system.
Adding equations (1) and (2), we get:
(-3x - 4y) + (3x - 5y) = -23 + 5
Simplifying, we get:
-4y - 9y = -18
-9y = -18
Dividing both sides by -9, we get:
y = 2
Now, substitute the value of y into either of the original equations. Let's substitute into equation (1):
-3x - 4(2) = -23
-3x - 8 = -23
Adding 8 to both sides:
-3x = -23 + 8
-3x = -15
Dividing both sides by -3, we get:
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 2.
Solve the system of two linear equations.%0D%0A−3x−4y=−23%0D%0A3x−5y=5(1 point)%0D%0AResponses
1 answer